2017
DOI: 10.1038/s41598-017-00982-3
|View full text |Cite|
|
Sign up to set email alerts
|

The role of the SWI/SNF chromatin remodeling complex in maintaining the stemness of glioma initiating cells

Abstract: Glioma initiating cells (GICs) are thought to contribute to therapeutic resistance and tumor recurrence in glioblastoma, a lethal primary brain tumor in adults. Although the stem-like properties of GICs, such as self-renewal and tumorigenicity, are epigenetically regulated, the role of a major chromatin remodeling complex in human, the SWI/SNF complex, remains unknown in these cells. We here demonstrate that the SWI/SNF core complex, that is associated with a unique corepressor complex through the d4-family pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
(48 reference statements)
1
26
0
Order By: Relevance
“…Although the complex is often described as a tumor suppressor role in multiple cancer types 15,24,26,59 , there is also increasing evidence for tumor-promoting functions of SWI/SNF in other malignancies, including leukemia, breast, liver and pancreas cancer, melanoma, glioblastoma, neuroblastoma and synovial sarcoma 25,[60][61][62][63][64][65] . In PCa, the role of SWI/SNF has long remained insufficiently characterized, but our study provides novel evidence that it can have tumor-promoting functions in PCa, including its most aggressive forms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complex is often described as a tumor suppressor role in multiple cancer types 15,24,26,59 , there is also increasing evidence for tumor-promoting functions of SWI/SNF in other malignancies, including leukemia, breast, liver and pancreas cancer, melanoma, glioblastoma, neuroblastoma and synovial sarcoma 25,[60][61][62][63][64][65] . In PCa, the role of SWI/SNF has long remained insufficiently characterized, but our study provides novel evidence that it can have tumor-promoting functions in PCa, including its most aggressive forms.…”
Section: Discussionmentioning
confidence: 99%
“…The GSK3β-USP22-LSD1 axis was validated in a cohort of clinical specimens from Grade IV GBM patients, where all three proteins showed increased levels of nuclear expression, significantly higher than their levels in a set of low-grade astrocytomas [98]. In the second study [99] the authors demonstrated that LSD1 participated in a co-repressor complex along with TLX and RCOR2 that was recruited by the SWI/SNF chromatin remodeling complex through the DPF1 and DPF3 adaptors [99]. A series of in vitro and in vivo experiments convincingly showed that this multi-protein complex played a major role in maintaining the stemness and promoting the tumor-initiating capacity of GSCs, probably through the repression of BMP2 and CDKN1A.…”
Section: Lds1 In Glioblastoma Stem Cellsmentioning
confidence: 98%
“…Repression of BMP2 and CDKN1A has been reported to be essential for stemness maintenance of GSCs [96,97]. Two studies uncovered different mechanisms that LSD1 utilized to silence these genes and suppress differentiation [98,99]. In the first study [98] they showed that increased nuclear levels of the β isoform of glycogen synthase kinase 3 (GSK3β) were responsible for the stabilization and accumulation of LSD1 by mediating its phosphorylation, a prerequisite for its binding and subsequent deubiqitination by ubiquitin-specific protease 22 (USP22).…”
Section: Lds1 In Glioblastoma Stem Cellsmentioning
confidence: 99%
“…We first tested the impact of the knockdown of each d4-family member on anchorage-independent growth using human cancer cell lines originating from non-small cell lung carcinoma (A549) (lacking BRG1 expression) and cervical tumor (HeLaS3) (competent for both BRG1 and Brm expression) using a series of short-hairpin (sh) RNAs 12 , 17 , 20 . All of these shRNAs expressed from lentivirus vectors were previously shown to suppress the corresponding mRNAs at least to 40% of those in cells carrying empty vector.…”
Section: Resultsmentioning
confidence: 99%